Integrating Ethnopedagogy and Cultural Arts Education: Preserving Indonesia's Heritage in the Globalized Era - Putra, Zakarias Aria Widyatama; Muryasari, Desiana; Medilianasari, Renistiara (Universitas Pendidikan Ganesha, 2024)
Ethnopedagogy is a modern approach to integrating local wisdom into education, aligning with the Merdeka Curriculum’s emphasis on cultural arts to counter Generation Z's detachment from Indonesia's heritage and prevent them from becoming passive technology users. This study aims to explore the relationship between ethnopedagogy and cultural arts education through qualitative research employing a literature-based approach. Data were collected from observations and documentation studies of reputable national and international journals. Thematic analysis was employed to investigate and contextualize ethnopedagogy’s integration within cultural arts education in the era of globalization. The findings highlight that ethnopedagogy fosters a holistic understanding of culture among students. Through cultural arts education, students develop skills and knowledge to connect local wisdom with the demands of the modern era. This study underscores the significance of ethnopedagogy as a foundation for arts education, promoting cultural literacy across all educational levels in alignment with governmental and institutional policies. Such an approach ensures that education contributes to preserving and revitalizing Indonesia’s cultural identity in a globalized world.